Effect of hydrothermal temperature treatment on the variance of fluorescence in Ca2SiO4:Tb3+ - Mani, Rajaboopathi (H. : ĐHQGHN, 2020)
Investigations of structural defects and their associated impact on the optical properties of optical materials are essential expediencies because different methods are involved in the preparation of those materials for display applications. Lanthanide ion doping is a simple structural probing strategy that facilitates the challenges of identifying the structural defects. Pure and terbium (Tb3þ) doped Ca2SiO4 (C2S) particles were prepared using Pechini (C2SP) and hydrothermal methods (C2SH). From SEM images, it is observed that the Tb3þ doped C2SP particles were highly agglomerated, more than the C2SH particles. The TEM study confirmed that the particle size decreased for C2SH prepared at the high hydrothermal temperatures of 180 and 200 C (C2S:180H and C2S:200H). Fluorescence emission quenching occurred for Tb3þ doped C2S:180H and C2S:200H. The emission intensity was high for Tb3þ doped C2SH prepared at 140 C compared to Tb3þ doped C2SP, C2S:180H and C2S:200H. The changes in the O2p orbitals, associated with the upper-level valence band spectra of the tetrahedral silicate of pure C2SP and C2S:180H, were experimentally evaluated in the X-ray photoelectron spectroscopy (XPS)-valence band spectra. The symmetry lowering owing to the distortion in the silicate unit quenched the emission, which was confirmed by XPS-valence band spectra and Tb3þ emission lines. This study suggests that the Pechini method is more suitable to prepare the Tb3þ doped C2S phosphors compared to the hydrothermal method, particularly at high temperature for solid state display and scintillator applications.